Songs of slavery and emancipation - Callahan, Mathew, 1951- (Margaret Walker Alexander series in African American studies., 2022)
"This project presents recently discovered songs composed by enslaved people and explicitly calling for resistance to slavery. Some originate as early as 1800 and others as late as the outbreak of the Civil War. The project also includes long-lost songs of the abolitionist movement, some of which were written by fugitive slaves as well as free black people, challenging common misconceptions of abolitionism"--